PENGARUH AKTIVITAS -GLUKOSIDASE EKTERNAL DARI KAPANG TERHADAP KADAR VANILIN BUAH VANILI - Dwi Setyaningsih, Kania Tresnawati, Maggy T. Soehartono dan A. Apriyantono (Jurnal Teknologi Industri Pertanian, 2006)
ABSTRACTVanilla is one of the most widely used and important flavoring materials wordwide. The Indonesian natural vanilla has known for having lower quality than Bourbon due to immature harvested bean and uncompleted curing process. The objective of this research was to increase the vanillin content of cured vanilla by improving the -glucosidase activity. This research studied the best mold (between Aspergillus niger and A. oryzae) and the optimum time for producing -glucosidase enzyme. The analysis was including the -glucosidase activity, vanillin and glucovanillin content, and reducing sugar content. The mold that produced the highest -glukosidase activity was A. niger with 72 incubation time was 193.7 unit/mg protein. The optimum pH and temperature of enzyme from A. niger was 4.5 and 60oC, respectively. The highest vanillin content produced from vanilla homogenat with enzyme extract A. niger at 18 hour incubation time was 0.514 mg/100 ml. The homogenate that is incubated with enzyme extract from A. niger has the highest glucose content at 48 hour incubation time (8.61 mg/ml). The glucovanillin content from three kind of homogenate was decreasing as long as incubation time from 0.44 mg/ml to 0.00 mg/ml (mold), from 0.26 mg/ml to 0.03 mg/ml (emulsin) and from 0.38 mg/ml to 0.12 mg/ml (endogen).Keywords : -glucosidase activity, vanillin, vanilla